The very best of : an excellent adventure [compact disc] - Jarreau, Al (Rhino Entertainment, 2009)
Along with jazz, Al Jarreau has won over fans in the pop and R & B world with his stunning vocal range. His entire career is chronicled with classic hits and a brand new track, Excellent Adventure.